Strategy of BAZNAS Tidore Islands City in Increasing Public Awareness to Pay Zakat to BAZNAS - Hamzah Muhammad; M. Zidny Nafi' Hasbi (Journal of Community Service and Rural Development, 2025)
This study aims to examine the strategy of BAZNAS in increasing public awareness of paying zakat. Along with the development of the times, public awareness in paying zakat has increased, although there are still those who give their zakat directly to mustahiq, but in its development it has experienced very significant growth. The method used in this study is a qualitative method. This type of research is field research, data collection used is by collecting data from the results of observations, interviews, and documentation. The location of this research is at BAZNAS, Tidore Islands City, North Maluku Province.